2001
DOI: 10.1164/ajrccm.163.6.2005116
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Wheezing in Very Young Children Is Associated with Lower Respiratory Inflammation

Abstract: Despite advances in understanding the pathophysiology of asthma, morbidity and mortality in pediatrics continue to rise. Little is known about the initiation and chronicity of inflammation resulting in asthma in this young population. We evaluated 20 "wheezing" children (WC) (median age 14.9 mo) with a minimum of two episodes of wheezing or prolonged wheezing > or = 2 mo in a 6-mo period with bronchoscopy and bronchoalveolar lavage (BAL). Comparisons were made with six normal controls (NC) (median age 23.3 mo)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
111
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(123 citation statements)
references
References 26 publications
6
111
1
5
Order By: Relevance
“…One such study compared the BAL findings in 6 healthy children compared to 20 subjects with recurrent wheezing or prolonged wheezing of greater than 2 months over a 6 month period. (Krawiec et al, 2001) In this report, the average age of the healthy children was 23 months compared to 15 months for the wheezing subjects. The wheezing subjects had a significantly greater number of total cells, lymphocytes, epithelial cells, neutrophils, and eosinophils compared to controls.…”
Section: Immunologic Determinants Of Severe Rsv Bronchiolitis In Humamentioning
confidence: 80%
See 1 more Smart Citation
“…One such study compared the BAL findings in 6 healthy children compared to 20 subjects with recurrent wheezing or prolonged wheezing of greater than 2 months over a 6 month period. (Krawiec et al, 2001) In this report, the average age of the healthy children was 23 months compared to 15 months for the wheezing subjects. The wheezing subjects had a significantly greater number of total cells, lymphocytes, epithelial cells, neutrophils, and eosinophils compared to controls.…”
Section: Immunologic Determinants Of Severe Rsv Bronchiolitis In Humamentioning
confidence: 80%
“…Wheezing subjects also had increased BAL levels of leukotriene (LT)B 4 and LTE 4 than control subjects. (Krawiec et al, 2001) LTB 4 is a neutrophil chemotactic factor. (Wenzel, 1997) LTE 4 is the final metabolite in the cysteinyl leukotriene pathway and has been shown to be an important mucus secretagogue, induce smooth muscle constriction, and be an eosinophil chemotactic factor.…”
Section: Immunologic Determinants Of Severe Rsv Bronchiolitis In Humamentioning
confidence: 99%
“…To design appropriate strategies, it is important to determine when relevant pathophysiologic elements of the disease begin to be expressed. From the standpoint of airway inflammation, recent work using both bronchoalveolar lavage in wheezing preschool children (14) and bronchial biopsy in infants (15) and young children (16) have demonstrated that both inflammatory cell infiltration and structural alterations (thickening of subepithelial reticular membrane) can be demonstrated by 2 to 3 years of life. Loss of lung function, predominantly noted in the persistent wheezing phenotype, occurs within the first 6 years of life (17).…”
Section: When Is the Right Time To Treat?mentioning
confidence: 99%
“…A asma Ă© uma entre as várias causas de sibilância nessa faixa etária 10 . Metade das crianças que sibilam no inĂ­cio da vida deixam de fazĂŞ-lo aos 6 anos de idade; sĂŁo os chamados sibilantes transitĂłrios, nos quais existe relação com a redução do calibre das vias aerĂ­feras, infecções virais de vias aĂ©reas superiores, tabagismo materno e fatores genĂ©ticos.…”
Section: Introductionunclassified